Cyber community empowerment policy as an effort to strengthen cyber defense - Dhiah Ayu Duwi Wahyuni; Tri Legionosuko; Sutrimo Sumarlan (Strategi Perang Semesta, 2022)
The universal people's defense and security system is a defense system that involves all citizens, territories, and other national resources, prepared by the government early, implemented in a total, integrated, directed, sustainable and sustainable manner for the sake of upholding the sovereignty, and territorial integrity of the Unitary State of the Republic of Indonesia and its protection. The safety of the entire nation and from various threats. Its hoped that this principle will become a loyal basis for the formulation of defense policies in Indonesia, including those related to cyber community empowerment. From this research, it is concluded that there is a need for testing, demonstration, and evaluation which haves several main functions in policy analysis.